Em torno do berço: discursos sobre a educação da infância pobre parahybana no Jornal A Imprensa (1912-1922) - Costa, Solanja Silva (2015)
This thesis has as its goal to investigate the discourses directed to the poor infancy education displayed in the newspaper A Imprensa between the years 1912 and 1922. Our interest is comprehend the idea of infancy, how it was educated and what the senses attributed to it by the parahybana society, clarifying the social expectations and looking for to build interfaces between the educational knowledges bound to schooling, to welfarism, to hygienism and to the moral of poor infancy. It was also investigated relations, ruptures and permanencies between the discourses directed to the poor infancy as well as the social places from where they part. As theoretical and methodological reference for this research, we adopt the so-called “Foucault tools”, mainly those that help us to comprehend the power and knowledges relations, which involve the discursive productions, and the truths transmitted in them. The analyzes point that the poor infancy, in the period from 1912 to 1922, were signified, in the discourses present in the newspaper A Imprensa through the enunciative and moral bias, the welfarism and hygienism, interpreted as essential devices for a wide formation of this subject, a condition considered primordial in order to this subject would become a civilized and productive citizen for the society. In order to reach this formation, the senses attributed to the parahybana poor infancy in the schooling discourse foresaw the State mandatory with infancy education; in the welfare discourse the centrality was the urgency of the public power to answer the charity welfare demands of the public in order to they to stay in the school; the hygienist discourse produced the helpless and sick infancy, which should be sanitized and regenerated and, finally, the moral discourse produced the indigent infancy taking as parameters the distance between the behavior standard stablished by that epoch society. They are discourses produced in the fights waged through the power, knowledge and truth relations which, at the same time that included the poor infancy, also promoted its exclusion, leaving deep marks in the way of thinking and organizing education.